Investigation of Cs surface layer formation in Cs‐SIMS with TOF‐MEIS and SIMS. (23rd June 2014) - Houssiau, L.; Noël, C.; Mine, N.; Jung, K. W.; Min, W. J.; Moon, D. W.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; et al.
<x xml:space="preserve">Abstract</x> In this report, cesium surface layers formed by Cs+ ion bombardment on silicon and phenylalanine (Phe) samples were analyzed by TOF‐MEIS and ToF‐SIMS. Si wafers were bombarded with 500 eV Cs+ ions, then were subsequently bombarded with five different Cs+ fluences corresponding to the transient and equilibrium regimes. The Phe layers were evaporated on Si wafers, up to 100 nm thickness. The samples were subsequently bombarded at four different fluences. For Phe, TOF‐MEIS shows the formation of a sharp Cs surface layer of 0.5 nm thickness, on which the peak height increases with Cs+ ion bombardment and a long Cs tail builds up, penetrating deep into the subsurface. For Si, a similar Cs surface peak forms, but it saturates quickly compared to Phe. Copyright © 2014 John Wiley & Sons, Ltd.